A reassessment of sustainability communication in Asian development initiatives - Gabai, Sara (Frontiers in Communication, 2025)
Sustainability communication plays a critical role in fostering behavior change, public engagement, and policy advocacy. However, existing research often under-theorizes the roles of culture, power, and localized narratives in shaping communication effectiveness, particularly in Asia. This paper explores how culturally attuned, multimodal communication strategies, ranging from social media campaigns to grassroots advocacy and strategic storytelling, can encourage participation and reduce the ‘psychological distance’ from sustainability challenges. Three communication cases from India, Myanmar, and Mongolia were analyzed to examine rhetorical strategies, narrative framing, and audience reception. Findings suggest that repositioning sustainability communication as a relational and transformational practice, rooted in intercultural understanding, can produce meaningful results. When the values of participants are genuinely acknowledged, and two-way dialogue is fostered, communication shifts from being instructional to collaborative. This shared process, grounded in local talents and stories, can lead to a stronger sense of ownership and pride in outcomes. The case studies include: a public transportation campaign in India, promoting electric vehicles and 4-stroke auto-rickshaws; a plastic bag reduction campaign launched in Myanmar’s local markets; and transmedia storytelling initiatives in Mongolia, conveying the stories of herders, and how they are collaborating to protect the rangeland and ensuring animal welfare nationwide. The paper argues that when communication is emotionally resonant, and structurally enabling – drawing on critiques of dominant discursive strategies in sustainability, hope-based communication theory, and participatory co-creation – it can support transformative change. It concludes with recommendations for communicators and scholars working at the intersection of sustainability and public engagement in the Global South.